Sugar-conditioned honey bees can be biased towards a nectarless dioecious crop - Estravis Barcala, Maria Cecilia (2024)
The targeted pollination strategy has shown positive results in directing honey bees to crop flowers offering nectar along with pollen as reward. Kiwifruit is a functionally dioecious species, which relies on bees to transport pollen from staminate to pistillate nectarless flowers. Following the targeted pollination procedures recently validated, we first developed a mimic odor (KM) based on kiwifruit floral volatiles for which bees showed the highest level of generalization to the natural floral scent, although the response towards pistillate flowers was higher than towards staminate flowers. Then, in the field, feeding colonies KM‐scented sucrose solution resulted in higher amounts of kiwifruit pollen collected by honey bees compared to control colonies fed unscented sucrose solution. Our results support the hypothesis that olfactory conditioning bees biases their foraging preferences in a nectarless crop, given the higher visitation to target flowers despite having provided the mimic odor paired with a sugar reward.